(3GdUdM ai GdOYhi GdLfGFjI (B/ s - (3Wg CMeO eMeO YHO GdYdjes; (3eCehf eMeO SdGeI (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2006)
(3TgOJ GdSfhGJ GdGNjQI GgJeGeG abgjG hJTQjYjG eJRGjOG HGdeLfi Ydjg (B: (3hHOhQg hMbhbg ai GdGLQGAGJ GdLfGFjI GP GJLg GdacQ GdLfGFi GdeYGUQ Gdi VeGf MUhd GdeLfi Ydjg Ydi Mbhbg cGedI (B: (3ef NdGd GbGeI GdeUGdMI hGdJhajb Hjfge hHjf GdLfGI hbO SGQ gPG GdGJLGg ai eSGQjf eJhGRjjf ai faS GdhbJ GhdgeG eSGQ JMbjb eUGdM GdeLfi Ydjg (B: (3hKGfjgeG eSGQ GjLGO HOGFd ddYbhHGJ GdJ`bdjOjI (B: (3hNGUI GdYbhHGJ GdSGdHI ddMQjIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2006.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ(B: 546- 585.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdOYhi GdLfGFjIs; (3CWQGa GdUdMs; (3GdUdM aj aQfSGs; (3GdUdM aj GdbGfhf GdHdLjcjs; (3GdUdM aj GdJTQjYGJ GdCfLdhScShfjgs; (3GdUdM aj GdbGfhf GdEfLdjRjs; (3GdUdM aj GdbGfhf GdCeQjcjs; (3GdUdM aj GdJTQjYGJ GdYQHjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs